A comprehensive analysis on effectiveness of compound parabolic collector and thermal enhancement using nanofluids - Mohammad Ishrar Jiva (22225249) (2025)
This review article examines two critical aspects of solar thermal energy: compound parabolic collectors (CPCs) and nanofluids. It evaluates CPC designs, especially when used with evacuated tube collectors, analyzing their impact on energy capture and system performance. The study also investigates nanofluids’ potential to enhance thermal conductivity in solar collectors. Current market trends and research patterns in CPC technology are explored, highlighting the underrepresentation of developing nations like India in this field. The article identifies areas for improvement, including optimized tracking systems and novel nanofluid compositions, concluding with a discussion on the broader implications for the solar energy sector and sustainable energy transition. Other Information Published in: International Journal of Low-Carbon Technologies License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1093/ijlct/ctae239